Try or Die: Dynamics of Plant Respiration and How to Survive Low Oxygen Conditions - Jay Jethva; Romy R. Schmidt; Margret Sauter; Jennifer Selinski (Plants, 2022)
Fluctuations in oxygen (O2) availability occur as a result of flooding, which is periodically encountered by terrestrial plants. Plant respiration and mitochondrial energy generation rely on O2 availability. Therefore, decreased O2 concentrations severely affect mitochondrial function. Low O2 concentrations (hypoxia) induce cellular stress due to decreased ATP production, depletion of energy reserves and accumulation of metabolic intermediates. In addition, the transition from low to high O2 in combination with light changes—as experienced during re-oxygenation—leads to the excess formation of reactive oxygen species (ROS). In this review, we will update our current knowledge about the mechanisms enabling plants to adapt to low-O2 environments, and how to survive re-oxygenation. New insights into the role of mitochondrial retrograde signaling, chromatin modification, as well as moonlighting proteins and mitochondrial alternative electron transport pathways (and their contribution to low O2 tolerance and survival of re-oxygenation), are presented.